At war within : the double-edged sword of immunity - Clark, William R., 1938- (Oxford University Press, 1995)
In the seventeenth century, smallpox reigned as the world's worst killer. Luck, more than anything else, decided who would live and who would die. That is, until Lady Mary Wortley Montagu, an English aristocrat, moved to Constantinople and noticed the Turkish practice of "ingrafting" or inoculation, which, she wrote, made "the small- pox ... entirely harmless." Convinced by what she witnessed, she allowed her six-year-old son to be ingrafted, and the treatment was a complete success--the young Montagu enjoyed lifelong immunity from smallpox. Lady Montagu's discovery would, ho